Circular RNA circ_0103552 forecasts dismal prognosis and promotes breast cancer cell proliferation and invasion by sponging miR‐1236. Issue 9 (5th May 2019) - Yang, Lixia; Song, Chang; Chen, Ying; Jing, Guilian; Sun, Jingwen
Abstract: Breast cancer (BC) is a fatal malignancy, which has a high incidence and mortality across the world. Circular RNAs (circRNAs) have crucial roles in tumor initiation and progression. In this project, a newly found circRNA, circ_0103552 was explored. Quantitative real‐time polymerase chain reaction was applied to measure its expression in the patients' tissue specimens and cells. In addition, Fisher's exact test, Kaplan‐Meier curves and Cox regression model were conducted to discover the clinical significance of circ_0103552. Cell viability, clone‐forming ability, apoptosis, and metastatic properties of BC cells were evaluated by gain/loss‐of‐function assays. Dual luciferase reporter assay was applied to illuminate its mechanisms. As data indicated, circ_0103552 was significantly elevated in BC tissue samples and cells. In addition, its expression correlates with clinical severity and dismal prognosis. Furthermore, circ_0103552 could facilitate cell growth, clone‐forming ability, migration and invasion, and decrease apoptotic cells. For the mechanism exploration, circ_0103552 could directly sponge miR‐1236 to execute oncogenic activities in BC cells. In summary, this study provides a novel circRNA in tumorigeneis and progression of BC and may help to develop effective therapeutic target for this devastating disease. Abstract : 1. Overexpressed circ_0103552 is correlated with breast cancer (BC) patients' clinical severity and poor prognosis. 2. circ_0103552 could directly sponge miR‐1236 in BC cells. 3. The oncogenic functions of circ_0103552 is partly dependent on its regulation on miR‐1236.